Rompi Penyedia Informasi bagi Penyandang Tunanetra Menggunakan Multisensor HC-SR04 - Widianto, Eko Didik; Ikhsan, M; Prasetijo, Agung Budi (Jurusan Teknik Elektro, Fakultas Teknik, Universitas Negeri Semarang, 2021)
Various electronic travel aids for people having visual impairment have been developed based on ultrasonic object detection employing the HC-SR04 ultrasonic proximity sensor. However, most of them do not consider blind spots where harmful objects cannot be detected. This study discusses the development of a vest that can detect objects in front of the blinds more widely and provide sound alert if an object in front is detected. This detector was developed based on an Arduino Uno equipped with five HC-SR04 ultrasonic sensors, and a mini DFPlayer module. In addition, blind area analysis of sensor detection is carried out to overcome objects that are not detected by similar studies. Horizontally, this travel vest sweeps objects up to 150 cm in distance with a 25o right or left angle deviation from forward direction. Vertically, object detection reaches up to 150 cm in distance with both upward and downward deviation of 30o from the vest.